(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2011)
We have used the density functional theory to make a predictive toxicity model of water soluble arsenicals. The structures are optimized for the minimum energy of the Schrödinger equation. From this optimized structure, we obtain the bond distance and angles of the stable structures. We have calculated vibrational frequencies, Ionization potential, atomic charges, electrophilicity and electron affinity of those arsenicals. The calculated vibrational frequencies and other physical properties are compared with those found from the different experiment. The mode of vibrational frequencies, electrophilicity and atomic charges (Mulliken) calculated for MMA(III) , DMA(III) ,arsenic acid, arsenous acid, MMA(V) and DMA(V) that follows acute toxicity of those arsenicals in laboratory animals. Raman micro-spectroscopy might also be showed its potential applications in the toxicology screening of chemicals and new biomaterials, with a range of cell types. Applying the model one could predict toxicity level of unknown water soluble arsenicals in future. Keywords : DFT; Raman spectroscopy; toxicity; Water soluble arsenicals; LD50 DOI: http://dx.doi.org/10.3329/bjsir.v46i2.6052 Bangladesh J. Sci. Ind. Res. 46(2), 177-182, 2011